PRELIMINARY STUDIES ON SEDIMENT CORE FROM THE TYRO BASIN - Geraga, M.; Anagnostou, Ch.; Iliopoulos, I.; Kontali, M. (Bulletin of the Geological Society of Greece, 2016)
The present paper summarizes the preliminary results of the mineralogical and micropaleontological analysis conducted on sediment samples from core TYR05 retrieved from the anoxic and hypersaline Tyro basin in the eastern Mediterranean Sea. The core comprises a complex lithostratigraphic sequence attributed to the strong geodynamic regime of the area. The planktonic foraminifera associations present fluctuations which coincide with changes in the lithology of the core. The mineralogical composition of the sediments shows influence from the evaporites developed on the bottom of the basin. The mineral constituents in association to the microfauna assemblages suggest that the sediments include sapropelic layers. Further analyses are needed in order to determine safely the sapropelic deposits.